Evaluation of Protein Creatinine Ratio as A Marker for Proteinuria among Children Recovered From Hypernatremia: A Longitudinal Observational Study (Bioresearch Communications, 2023)
Background: Proteinuria is one of the many markers of kidney damage. An increased protein creatinine ratio (Pr/Cr ratio) is known to have both diagnostic and prognostic value in detecting renal damage. The previous observational study revealed that children with hypernatremia are at risk of developing acute kidney injury (AKI), which positively correlates with recovery from hypernatremia. Detection of high Pr/Cr ratio in the spot urine samples is a predictor for proteinuria. However, there is lack of evidence for whether or not renal damage persists in children who recovered from hypernatremia. Therefore, we aimed to evaluate the long-term renal function of the children who had recovered from hypernatremia.Methodology: The study was an observational longitudinal study conducted in Dhaka Hospital of icddr,b from March 2016 to March 2017. The objective of this study was to evaluate the renal function of children 12 months after recovering from hypernatremia. All these children in this cohort study were brought to Dhaka Hospital of icddr,b for a spot urine analysis to evaluate their kidney function.Results: Among the 224 children who recovered from hypernatremia 143 (64%) children’s mothers gave consent to participate in follow-up study. Half of the study children demonstrated to have a raised urinary Pr/Cr ratio. However, majority of them did not have any evidence associated with urinary problems. Proteinuria was comparable in different types of hypernatremic children. After adjusting for potential co-variates like age, sex, any form of malnutrition, severity of hypernatremia and co-morbidity, 86% of children from better socioeconomic family are less likely to have high urinary Pr/Cr ratio in comparison with those from poorest households. Regression analysis also revealed that children who were less than 36 months of age are 2 times more likely to have raised urinary Pr/Cr ratio than those more than 36 months old (Odds Ratio 2.31(1.06, 5.02); p 0.035).Conclusion: Children from low socioeconomic households and below 36 months of age are more likely to have proteinuria after recovering from hypernatremia. However further study is required to correlate the high Pr/Cr ratio with other parameters to rule out the long-term effect of hypernatremia on renal function.Bioresearch Commu. 9(2): 1270-1275, 2023 (July)